Diagnostics and treatment of Clostridium difficile-associated disease: Guidelines of the Russian gastroenterological association - V. T. Ivashkin; N. D. Yushchuk; I. V. Mayev; Tatyana L Lapina; Ye. A. Poluektova; O. S. Shifrin; A. S. Tertychny; A. S. Trukhmanov; A. A. Sheptulin; Ye. K. Baranskaya; O. S. Lyashenko; K. V. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of publication. To present with clinical guidelines of the Russian gastroenterological association on Clostridium difficile-associated disease management to practical doctors. Summary. Clostridium difficile-associated disease develops at disorders of intestinal microbiome with excessive colonization of C. difficile which toxins cause colonic inflammation and damage. C. difficile toxins A and B are major virulence factors causing damage of intestinal wall and inflammation due to damage of intestinal epithelial barrier, induction of proinflammatory cytokines, apoptosis and a necrosis of epithelial cells. Current epidemiologic trends of C. difficile-associated disease are characterized by growth of both inpatient and community-acquired morbidity, expansion of risk groups, increase in number of more severe cases including those, caused by more virulent BI/NAP1/027strain, tendency to relapsing, increase in lethal outcomes. C. difficile infection is the most common cause of intrahospital diarrhea leading to significant mortality. Risk factors of C. difficile-associated include antibacterial therapy, hospital admission, elderly age, comorbidity and immunosuppressive treatment. At the present time several laboratory methods for diagnosis of Clostridial infection exist: fecal ELISA test for toxins A and B, PCR, test for C. difficile glutamate dehydrogenase. Detection of densely adhered to underlying mucosa greenish or creamy deposits (pseudomembranes) is the endoscopical marker of severe C. difficile-associated disease i.e. pseudomembranous colitis. C. difficile-associated disease treatment includes vancomycin and metronidazole, the choice of drug and dose depends on disease severity. Significance of sorbents and probiotics in patient management is under discussion. Prophylaxis requires rational application of antibiotics, decrease, whenever possible, of terms of hospital stay, timely diagnosis and observance of sanitary and epidemiologic rules in medical institutions. Conclusion. Epidemiologic growth, risk of significant morbidity made C. difficile-associated disease a socially important disease. The present guidelines direct the doctor to correct diagnosis and adequate treatment of C. difficile infection.